Transmigration: the rise of flexible migration strategies as part of superdiversity. (27th October 2017) - Geldof, Dirk; Schrooten, Mieke; Withaeckx, Sophie
Abstract : Superdiversity implies increasing diversity within diversity, including the rise of flexible migration strategies: complex migration trajectories implying serial cross-border mobility between two or more countries. The article explores transmigration in the two main superdiverse Belgian cities of Brussels and Antwerp, based upon in-depth interviews with Brazilian, Ghanaian and Moroccan transmigrants. The article analyses the social problems related to transmigration, how these problems transcend borders and challenge urban social work and social policies at different levels. It explores why transmigration requires forms of multilevel governance to deal with people living beyond borders in the EU.